Antioxidant capacity of lourteigia stoechadifolia (L. F.) R.M. King & H. ROB. Asteraceae (2019)
This study aimed to evaluate Antioxidant Capacity of extracts and fractions obtained from Lourteigia stoechadifolia (L. f.) R.M. King & H. Rob. Asteraceae, leaves using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) methods. Extracts were obtained in dichloromethane and ethanol, using Soxhlet extraction, subsequent, a solid-liquid fractionation with solvents of increasing polarity has been carried out: Hexane, Chloroform, and Methanol for each of the extracts; antioxidant capacity were evaluated for each fraction and extract. Using the DPPH method, the ethanolic extract showed a relative antioxidant capacity equivalent to ascorbic acid of 28.6 and it’s methanolic fraction of 32.0, and using the ABTS method, the ethanolic extract showed a relative antioxidant capacity equivalent to ascorbic acid of 58.5 and its methanolic fraction of 49.8. The ethanolic extract and its methanolic fraction showed the highest antioxidant capacity, these data show a potential of free radical scavengers, property that can be exploited in the cosmetic and food industry.